Dynamics of changes in immunological parameters in adults with COVID-19 - O. M. Olenkova; O. P. Kovtun; Yu. G. Lagereva; Ya. B. Beikin (Журнал инфектологии, 2023)
Aim. To evaluate the immune response in patients with COVID-19 and to track the dynamics of changes in immunological parameters 2-3 weeks after the onset of the disease.  Materials and methods. The study included the results of a survey of 55 people aged 19 to 55 years with a new coronavirus infection (NCVI, COVID-19) in 2020. 27 of them were re-examined. The first sample (n=55) was taken on average 4.3 ± 0.49 days from the onset of the disease, the second (n=27) – 12.7 ± 1.12 days. The control group consisted of practically healthy individuals (n=41). The following indicators were determined in all patients: the presence of SARSCoV-2 RNA, the parameters of the general blood test, the main subpopulations of lymphocytes, the level of total immunoglobulins (IgM, IgG, IgA), the number of CEC, the absorption and bactericidal activity of leukocytes, the level of specific IgM and IgG to SARS-CoV-2.  Results. At the onset of the disease, a statistically significant decrease in the level of lymphocytes (p<0.001) and their subpopulations (TNK cells (p<0.001), T-helper lymphocytes (<0.001), cytotoxic T-lymphocytes (p<0.001), NK cells (<0.001) and T-lymphocytes (<0.001)). At the same time, the level of activated T-lymphocytes was statistically significantly higher (p<0.001) than the same indicator in the control group. When analyzing immunological parameters after 12.7±1.12 days, an increase in the total number of lymphocytes (p<0.001), T-lymphocytes (p=0.003), T-helper cells (p=0.015) was found; an increased content of activated T-lymphocytes (p<0.001) and a low level of TNK cells (p<0.001). The indicators of the phagocytic link in patients with COVID-19 in the first days of the disease were within the reference range (similar indicators in the control group). Repeated examination of patients (sample 2) showed an increase in the phagocytic activity of leukocytes and monocytes (p<0.003 and p<0.09, respectively). At the beginning of the disease, already on the 4th-5th day of the disease, specific IgM and IgG antibodies to SARS-CoV-2 were detected in the blood serum of patients, by the second week of the disease their level was significantly higher than in the first study (p<0.009).  Conclusion. At the onset of the disease, insufficiency of the cellular link of immunity was noted, which is probably as sociated with a violation of immunoregulatory mechanisms. At the same time, an increase in the level of activated T-lymphocytes indicates an overactivation of immune reactions, i.e. it can be said that there is an imbalance in the immune response in COVID-19.